توظيف النص القرآني في المحتوى التعليمي وأثره في تعليمية اللغة العربية - بن فردية، ضياء الدين Bin Fardiah, Diauldin; البار، عبدالقادر Albar, Abdulqader (جامعة مولود معمري تيزي وزو - مخبر الممارسات اللغوية, 2022)
هدفت هذه الدراسة إلى التعرف على مدى فاعلية توظيف النص الديني القرآني في المحتوى التعليمي اللغوي، وأثر ذلك في تعليمية اللغة العربية، ضمن إشكالية مفادها: إلى أي مدى يسهم النص الديني القرآني في فاعلية تعليمية أنشطة اللغة العربية؟ وقد تناول البحث عدة نقاط لتغطي إشكاليته، من تعريف للمحتوى التعليمي واختياره، وتعليمية اللغات في جانبها الاصطلاحي المفاهيمي بصفة عامة، وتعليمية اللغة العربية بصفة خاصة، إضافة إلى دور النص القرآني في اللغة العربية بوجه عام، ودوره في تعليميتها بوجه خاص، وخلصنا في نهاية البحث إلى أن للنص القرآني دورا فعالا في تعليمية اللغة العربية من خلال جوانب متعددة تتعلق بمتعلم العربية على وجه التحديد. This study is aiming at identifying the effectiveness of using the Quranic text in linguistic educational content, and the effect of that on teaching Arabic language, within the following problematic : To what extent does the Quranic text contribute to the educational effectiveness of Arabic language activities? The paper deals with several points to well investigate the problematic: definition of educational content, as well as language teaching in its conceptual terminology aspect in general And the teaching of the Arabic language in particular, in addition to the role of the Quranic text in the Arabic language in general, and its role in the very language teaching in particular. We concluded at the end of the research paper that the Quranic text plays an effective role in the teaching of the Arabic language through various aspects related specifically to the Arabic learner
Keywords: اللغة العربية -- القراّن الكريم -- اللسانيات النصية -- المناهج التعليمية